IDEOLOGI KAPITALISME SASTRA POPULER DALAM NOVEL CINDERELLA MAN KARYA MARC CERASINI - Adi Prautomo (Prodi Pendidikan Bahasa dan Sastra Indonesia, Universitas Balikpapan, 2020)
This research is entitled Ideology of capitalism of popular literature in the novel Cinderella Man. The formulation of the problem is how the formula is contained in the novel Cinderella Man. The formula as a stereotype that is popular culture can be seen in the characters and settings. This study aims to describe and analyze the formula contained in the novel, also describes the ideology of capitalism. The method used in this study is descriptive qualitative research method by using a textual approach by utilizing the formula theory introduced by Cawelti. The data source used in this study is the novel Cinderella Man by Marc Cerasini. Moreover, the results of this study indicate in this novel the storyline (functional analysis) is by what is stated in Cawelti's theory of formula in popular literature. This novel implies values toward humans including ideological values, and the value of coexistence among humans.